UPAYA MENINGKATKAN MOTORIK KASAR ANAK DENGAN PERMAINAN TRADISIONAL GOBAK SODOR KELOMPOK B DI TK CEMPAKA GLANTANGAN KECAMATAN TEMPUREJO JEMBER - Ana Rusdiana, Ana Rusdiana; Wijaya Adi Putra; Muhammad Agus Sugiarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This traditional game of gobak sodor was played as an effort to improve the gross motor skills of Group B children at Cempaka Glantangan Kindergarten in Tempurejo District, Jember Regency, as well as to introduce traditional games that are rarely played by children nowadays. This study was conducted using the Classroom Action Research (CAR) method. The subjects of this study were the students of Group B at TK Cempaka Glantangan in Tempurejo District, Jember Regency, consisting of 15 children, including 4 boys and 11 girls. The initial research results conducted in the pre-cycle stage showed a lack of gross motor skills in children, with a percentage of 33.33% or falling into the “Beginning to Develop” (MB) category. The research results conducted in Cycle I obtained a percentage of 53.33% and were still in the “Beginning to Develop” (MB) category. Meanwhile, the results of the research in Cycle II showed an improvement in the children's gross motor skills by 86.66%, which falls into the “Developing as Expected” (DE) category. From these research results, it can be concluded that playing the traditional game of gobak sodor can improve the gross motor skills of Group B children at TK Cempaka Glantangan in Tempurejo District, Jember Regency.